Broadening versus reinforcing investor portfolios: Social structure and the search for venture capital investors - Wang, Pengfei (Journal of Business Venturing, 2020)
This paper highlights the venture capital investor (VC) portfolios of startups, and explores how the portfolios evolve. We emphasize the important trade-off between broadening and reinforcing VC portfolios (i.e., expanding to new VCs versus relying on existing VCs). This is because, to startups, new and existing VCs generate very different opportunities and constraints. Focusing on the social structure of existing VCs, we argue that startups are more likely to opt for new VCs when the internal networks of existing VCs are denser, when the external networks of existing VCs are smaller, and when the status of existing VCs is lower. Additionally, we not only focus on whether new VCs are on board, but also pay attention to which new VCs are introduced, by analyzing the ex-ante embeddedness between existing and newly-introduced VCs. We stress that when new VCs are highly embedded with existing VCs, their involvement makes only a limited contribution to broadening a startup's portfolio and network. We test the hypotheses using a sample of VC financing rounds in the U.S. and find broad support.